Reasons why the diagnosis of serrated polyposis syndrome is missed. Issue 3 (March 2019) - van Herwaarden, Yasmijn J.; Pape, Simon; Vink-Börger, Elisa; Dura, Polat; Nagengast, Fokko M.; Epping, Ludger S.M.; Bisseling, Tanya M.; Nagtegaal, Iris D.
Abstract : Objectives: Serrated polyposis syndrome (SPS) is a relatively new and under-recognized colorectal cancer (CRC) predisposition syndrome. Previous studies have reported miss-rates of SPS diagnosis varying from 40 to 82%. As SPS patients and their first-degree relatives have an increased risk of CRC, early recognition is important. We aimed to determine the miss-rate of SPS and to determine the reasons for missed diagnosis. Patients and methods: We retrospectively identified all patients diagnosed with at least one colorectal polyp or carcinoma detected at our tertiary referral center between January 1986 and July 2013 using the nationwide pathology registry. On the basis of cumulative polyp count with size and location, SPS patients were identified. We checked whether the SPS diagnosis was made in the medical files and, if not, what might have been the reason for missing the diagnosis. Results: We randomly assessed 5000 patients, of whom 25 patients fulfilled the WHO criteria for SPS. In six patients, no previous SPS diagnosis had been made, leading to a miss-rate of 24.0% (95% confidence interval: 7.3–40.7). The reasons for missed diagnosis were polyps removed before establishment of the WHO criteria, unavailable pathology reports, and failure to apply the criteria by the clinician. Conclusion: The miss-rate for the diagnosis of SPS is considerable, even during longer follow-up with repeated colonoscopies. A preventable reason for missing SPS cases is failure to apply the WHO criteria. Awareness of this CRC predisposition syndrome needs to be raised to decrease the miss-rate of SPS.